2019
DOI: 10.3390/w11122529
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Modelling Soil Evaporation in an Irrigated Olive Orchard to Improve Water Management

Abstract: The aim of this study was to estimate soil evaporation (Es) in an intensive olive orchard. Measurements of Es were performed for 19 days using microlysimeters, during summers 2010, 2011 and 2012 in southeast Portugal. In order to relate each area type to radiation transmissivity, ground cover measurements were performed over the years. These data were used to calibrate and validate an empirical model for Es estimation. Measured daily average Es was 0.55 ± 0.14 mm; the model estimated 0.53 ± 0.18 mm for the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…López-Olivari et al [44] evaluated the partitioning of actual evapotranspiration in soil evaporation and transpiration over a superintensive drip-irrigated olive orchard in Cile and found that ratios of transpiration and soil evaporation to actual evapotranspiration ranged ranged between 0.64-0.74 and 0.26-0.36. Tezza et al [45] measured and modelled soil evaporation in olive orchards in Portugal and found that, during a typical summer, the ratio between soil evaporation and canopy transpiration was 0.3 on average, and the ratio between soil evaporation and evapotranspiration ranged between 0.3 and 0.15. However, they also asserted that "the complexity of the canopy geometry with variable positional shadings along the days and seasons, overlapping with the individual geometry of the wet surfaces and variable turbulence, makes it very difficult to generalize models for evaporation below crowns"; in other words, the canopy plays an important role in the evapotranspiration process.…”
Section: Discussionmentioning
confidence: 99%
“…López-Olivari et al [44] evaluated the partitioning of actual evapotranspiration in soil evaporation and transpiration over a superintensive drip-irrigated olive orchard in Cile and found that ratios of transpiration and soil evaporation to actual evapotranspiration ranged ranged between 0.64-0.74 and 0.26-0.36. Tezza et al [45] measured and modelled soil evaporation in olive orchards in Portugal and found that, during a typical summer, the ratio between soil evaporation and canopy transpiration was 0.3 on average, and the ratio between soil evaporation and evapotranspiration ranged between 0.3 and 0.15. However, they also asserted that "the complexity of the canopy geometry with variable positional shadings along the days and seasons, overlapping with the individual geometry of the wet surfaces and variable turbulence, makes it very difficult to generalize models for evaporation below crowns"; in other words, the canopy plays an important role in the evapotranspiration process.…”
Section: Discussionmentioning
confidence: 99%
“…Trees of the first experiment (Figure 2a) located near Ferreira do Alentejo had the following characteristics: 7-years old, drip irrigation, 300 trees/ha, LAI between 1.01 in 2010 (Häusler et al, 2014) and 1.61 in 2012 (Tezza et al, 2019), ground cover ≈ 20%, height between 3.2 and 3.5 m (Conceição et al, 2017).…”
Section: Methodsmentioning
confidence: 99%